Linguistic insights into attitudinal stance in Russian philology thesis reviews - Olga A. Boginskaya (Peoples' Friendship University of Russia (RUDN University), 2024)
In the academic landscape, where knowledge is constantly debated, reviews serve as crucial navigational tools. The critical analyses not only evaluate previous studies but also reveal the reviewer's own stance towards them. Drawing upon a corpus of 124 philology thesis review reports published in 2020-2024, this study explores the process of stancetaking in evaluative academic discourse through the use of attitude markers. The aim of the study is to analyse the predominant types, frequencies and lexical-grammatical categories of linguistic items used by Russian thesis reviewers to take attitudinal stance. The instances of attitude were identified based on Mur-Dueñas's typology, including three groups - significance, assessment, and affect. The findings revealed that attitude markers constitute an integral part of thesis reviews, helping verify scientific knowledge and conferring authority and authenticity upon dissertations by evaluating their quality and value to the field. The most frequent attitude markers found in the corpus were assessment resources predominantly realised through adjectives and adverbs. Significance markers ranked second and were presented by adjectives and nouns. Affective stance was infrequent in the corpus, and the range of emotions was not so wide, including a limited number of affective states such as interest, surprise, regret, disappointment, joy, and approval. Affective stance was realised through adjectives, adverbs, nouns, verbs, and nominal phrases. The analysis also showed that negative assessments were mitigated in most cases through the use of hedges, while positive attitudes were amplified through the use of boosters.